The Influence of Home Atmosphere and EFL Interest on Students’ Performance in Writing Final Project - Anggianti, Ratna; Deni Wijayatiningsih, Testiana; Setiawan, Anjar (Universitas Muhammadiyah Semarang, 2024)
This study examines the influence of Home Atmosphere and EFL Interest on Students' Performance in Writing Final Projects. The research aims to understand how these factors contribute to students' success in academic writing within an English as a Foreign Language (EFL) context. A sample of 150 EFL students participated in the study, completing surveys measuring their home atmosphere, interest in EFL, and writing performance. The study employed a quantitative approach, utilizing correlation analysis and multiple regression. Results indicate strong positive correlations between Home Atmosphere and Writing Performance (r = 0.68), and between EFL Interest and Writing Performance (r = 0.75). Multiple regression analysis revealed that both Home Atmosphere (β = 3.2, p < 0.001) and EFL Interest (β = 4.1, p < 0.001) significantly predict Writing Performance. The model explains 72% of the variance in Writing Performance (R-squared = 0.72). These findings suggest that both a conducive home environment and a high level of interest in EFL play crucial roles in students' ability to write effective final projects. The study contributes to the understanding of factors influencing academic writing in EFL contexts and provides implications for educational practices and policies aimed at improving students' writing performance.